THE UKRAINIAN OF «POETIC CINEMA»: THE SCREEN TRANSFORMATION OF M. KOTSIUBYNSKYT’S NARRATIVE «SHADOWS OF FORGOTTEN ANCESTORS» - Хороб, С. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the problems of Ukrainian «poetic cinema» in connection with the screen adaptation of Mykhaylo Kotsiubyns’kyi’s narrative «Shadows of Forgotten Ancestors». It is proved that the film made on the basis of the work of the Ukrainian literature classic became a landmark in creating not the school but the system of the national «poetic cinemato-graphy», that elements of its poetics and aesthetics can be surveyed in other motion pictures, which have a perfect right to be referred to such a type of «poetic cinema» not only inside, but also outside Ukraine.